2008
DOI: 10.3928/00220124-20081001-03
|View full text |Cite
|
Sign up to set email alerts
|

A Process of Becoming: The Stages of New Nursing Graduate Professional Role Transition

Abstract: Newly graduated nurses are entering the work force and finding that they have neither the practice expertise nor the confidence to navigate what has become a highly dynamic and intense clinical environment burdened by escalating levels of patient acuity and nursing workload. This research used qualitative methods to build on and mature aspects of the new nurse's transition experience into acute care. The theory of transition presented in this article incorporates a journey of becoming where new nursing graduat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
466
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(506 citation statements)
references
References 33 publications
34
466
0
6
Order By: Relevance
“…The six month decline in job satisfaction, organizational commitment, and clinical decision-making are consistent with findings in the literature (Altier & Krsek, 2006;Duchscher, 2008;Casey, Fink, Krugman & Propst, 2004;Goode, et al, 2009;Krugman et al, 2006). In particular, Casey et al (2004) found that the most difficult role adjustment time was between six to twelve months after hire.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The six month decline in job satisfaction, organizational commitment, and clinical decision-making are consistent with findings in the literature (Altier & Krsek, 2006;Duchscher, 2008;Casey, Fink, Krugman & Propst, 2004;Goode, et al, 2009;Krugman et al, 2006). In particular, Casey et al (2004) found that the most difficult role adjustment time was between six to twelve months after hire.…”
supporting
confidence: 77%
“…This may reflect that new graduates are still in the shock phase and grappling with their professional role transition and have yet to enter the resolution and recovery phases as identified by Kramer (1974) and Duchscher (2008). However, significant increases from midpoint to program end does lend support for the value of residency programs since it may demonstrate the influence of the program to expedite the new graduates' recovery of disillusionment and questioning that occurs in this middle phase of the transition experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They expressed feeling overwhelmed and, in many instances, ill-prepared to move to NQN roles. Increasing research interest in this transition to NQN in general has led to the development of theoretical frameworks to better understand the nature of the transition (see for example, Duchscher, 2008Duchscher, , 2009. However, there is comparatively little evidence concerning the impact of previous employment as a HCSW on this transition.…”
Section: Transition To Newly Qualified Nursementioning
confidence: 99%
“…[13] Affection Facing life and death situation of critical ill patient, interpersonal relationship with paramedical staff, and adapting to hierarchical nursing culture are some significant challenges which lead to psychological burden on new graduates. [14] Therefore two identical sessions of 'principles and application of self-help, cognitive-behavioral therapy and mindfulness-based wellness resilience' are arranged to promote self-awareness, self-compassion, healthier life with more adaptive lives, and awareness of dysfunctional thoughts and cognition, by applying basic cognitive therapy techniques to alleviate psychological distress. In addition, life and death education is also offered to strengthen skills in handling life-and-death situations.…”
Section: Knowledge and Skillsmentioning
confidence: 99%